Su alcuni aspetti della congiuntura e della politica monetaria italiana nell' ultimo quinquennio. (Inflation, balance of payments deficit and their cure through monetary policy: the Italian example) - F. MODIGLIANI; G. LA MALFA (Moneta e Credito, 2014)
There appears to be a rather wide agreement among Italian economists, in and out of the Government, on the causes of Italy’s balance of payments crisis and of the recession that began in 1964. This explanation, originally put forward by the Bank of Italy, though rather unsatisfactory, has been uncritically accepted or at least has not been challenged in any systematic way. The present paper assesses the validity of this explanation and proposes an alternative one. For the sake of simplicity the authors keep separate the case of an open economy from that of a closed one. The Bank of Italy’s model is first formalised before its basic shortcomings are demonstrated. The authors then present the alternative model they propose. The nature of the Italian inflation and the determinants of wage movements are then discussed. The authors then consider the case of an open economy before provided a formal treatment of the problems raised.